AGAMA SEBAGAI REALITAS PENYEIMBANG BAGI MANUSIA PERSPEKTIF GUSTAV JUNG - Utang, Herman Y. (Pastoralia Jurnal Penelitian Dosen, 2023)
Humans are multi-dimensional creatures. He seeks unity and balance in paradoxical dimensions. Gustav Jung, the psychologist, ventured into the world of psychoanalysis with Freud and discovered the recesses of the human soul which are structured between conscious and unconscious aspects. Religion in Gustav Jung's view is an unconscious and individual reality that can build human self-balance in the midst of paradoxical factions. Researchers try to discover the essence of Gustav Jung's basic concept about the nature of religion from Jung's perspective and the role of religion in human paradoxical reality. The research method used in this research is qualitative descriptive using Gustav Jung's psychoanalytic approach.The results of this research show that religion for Jung is a human self-projection of unity. Humans psychologically long to be in that unity or perfection. Selfprojection towards religion is appropriate because it is religion that has God as a reality that surpasses all human abilities.